Unsolved Problems in Ecology - Dobson, Andrew; Holt, Robert D.; Tilman, David (Princeton University Press, 2020)
Leading ecologists discuss some of the most compelling open questions in the field todayUnsolved Problems in Ecology brings together many of the world's leading ecologists to discuss the most fundamental research questions confronting the field today. This diverse and thought-provoking collection of essays spans virtually all of the key subfields of the discipline, from behavioral and evolutionary ecology to population biology, community ecology, ecosystem ecology, disease ecology, and conservation biology. These essays are intended to stoke curiosity, challenge prevailing wisdom, and provoke new ways of thinking about ecology in light of new technologies and unprecedented environmental challenges brought on by climate and land-use change. Authoritative and accessible, Unsolved Problems in Ecology is ideal for graduate students in the early stages of their scientific careers and an essential resource for seasoned ecologists looking for exciting new directions to take their research.Sheds light on modern ecology's most important and compelling open questionsFeatures thought-provoking contributions from more than two dozen world-class ecologistsCovers behavior, evolution, communities, ecosystems, resource management, and moreDiscusses ways to raise the financial and intellectual profile of the disciplineAn invaluable resource for graduate students as well as seasoned ecologists